Brandtodinium gen. nov. and B. nutricula comb. Nov. (Dinophyceae), a dinoflagellate commonly found in symbiosis with polycystine radiolarians. Issue 2 (19th March 2014) - Probert, Ian; Siano, Raffaele; Poirier, Camille; Decelle, Johan; Biard, Tristan; Tuji, Akihiro; Suzuki, Noritoshi; Not, Fabrice; Lane, C.
<x xml:space="preserve">Abstract</x> Symbiotic interactions between pelagic hosts and microalgae have received little attention, although they are widespread in the photic layer of the world ocean, where they play a fundamental role in the ecology of the planktonic ecosystem. Polycystine radiolarians (including the orders Spumellaria, Collodaria and Nassellaria) are planktonic heterotrophic protists that are widely distributed and often abundant in the ocean. Many polycystines host symbiotic microalgae within their cytoplasm, mostly thought to be the dinoflagellate Scrippsiella nutricula, a species originally described by Karl Brandt in the late nineteenth century as Zooxanthella nutricula. The free‐living stage of this dinoflagellate has never been characterized in terms of morphology and thecal plate tabulation. We examined morphological characters and sequenced conservative ribosomal markers of clonal cultures of the free‐living stage of symbiotic dinoflagellates isolated from radiolarian hosts from the three polycystine orders. In addition, we sequenced symbiont genes directly from several polycystine‐symbiont holobiont specimens from different oceanic regions. Thecal plate arrangement of the free‐living stage does not match that of Scrippsiella or related genera, and LSU and SSU rDNA‐based molecular phylogenies place these symbionts in a distinct clade within the Peridiniales. Both phylogenetic analyses and the comparison of morphological features of culture strains with those reported for other closely related species support the erection of a new genus that we name Brandtodinium gen. nov. and the recombination of S. nutricula as B. nutricula comb. nov.